Disminución de la agudeza visual y su incidencia en afecciones oftalmológicas en adultos del centro de salud San Carlos, cantón Quevedo, Provincia Los Ríos, periodo septiembre 2017 a febrero 2018. - Calero Gaibor, Martin Fernando (2018)
The present study was carried out at the San Carlos Health Center, with the aim of determining the causes of the decrease in visual acuity in adults of the place, considering the incidence of ophthalmological conditions, during the period from September 2017 to February 2018, for effect, a field study was implemented to identify those conditions associated with the visual acuity of the patients, research that was reinforced with the documentary study, based on the variables of the study object, in the same way the following aspects were evaluated; sex, age, occupation, history, measures of visual acuity, refraction, diagnosis, ophthalmological affection and alternative solutions were established to the defined problem, this with the purpose of determining the causes of the problem. Analyzing the results obtained through the field study, it is determined that there are ophthalmological conditions that affect the visual acuity of adults, and that these drawbacks are caused by the lack of care, prevention, among other determining factors, that is why the This document presents an ophthalmological prevention and care guide to improve visual acuity and control the conditions that affect the vision of adults. It is considered that the proposed proposal is an alternative solution to the problem diagnosed, especially in regard to vision care. To achieve the objectives of the project, the most suitable types, methods, techniques and research instruments were used, which determined the problem and led to the establishment of an effective solution alternative.